2016
DOI: 10.4081/ecj.2016.5659
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute lactic acidosis and hypoglycemia due to isolate tramadol poisoning

Abstract: The article describes a case of severe acute lactic acidosis and hypoglycemia after intentional ingestion of tramadol overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
3
1
0
Order By: Relevance
“…Conflicting results have been reported in several studies. Some studies have reported hypoglycemia in tramadol poisoning [5,8,[27][28][29][30][31][32][33][34][35][36] and others have reported elevated blood glucose levels in these individuals [31,37,38]. Consistent with our results, several studies have shown normal blood glucose levels in people with tramadol poisoning [4,8,31,34,36,39,40].…”
Section: Discussionsupporting
confidence: 91%
“…Conflicting results have been reported in several studies. Some studies have reported hypoglycemia in tramadol poisoning [5,8,[27][28][29][30][31][32][33][34][35][36] and others have reported elevated blood glucose levels in these individuals [31,37,38]. Consistent with our results, several studies have shown normal blood glucose levels in people with tramadol poisoning [4,8,31,34,36,39,40].…”
Section: Discussionsupporting
confidence: 91%
“…Con icting results have been reported in several studies. Some studies have reported hypoglycemia in tramadol poisoning [5,6,[23][24][25][26][27][28][29][30][31][32], and others have reported elevated blood glucose levels in these individuals [6,24,33,34]. Consistent with our results, several studies have shown normal blood glucose levels in people with tramadol poisoning [4, 6, 23-25, 35, 36].…”
Section: Discussionsupporting
confidence: 90%
“…There is significant heterogeneity in the types of literature reporting tramadol-associated hypoglycemia especially with trial design, statistical tests, covariates, and study inclusion and exclusion criteria. 4,6-17 Two case-control studies of diabetic and nondiabetic patients by Golightly et al 13 and Fournier et al 9 support our findings that there is a stronger signal for tramadol-associated hypoglycemia in patients not taking diabetes medications. Golightly et al reported an increased risk of hypoglycemia in tramadol patients who were not diabetic compared with oxycodone patients with hypoglycemia who were not diabetic (RR = 3.12 [95% CI = 1.53-6.51]).…”
Section: Discussionsupporting
confidence: 71%
“…There have been 12 reports published about tramadol-induced hypoglycemia in English between 2009 and 2018 representing the United Kingdom, the United States of America, Australia, India, Saudi Arabia, Qatar, Iran, France, Nigeria, Italy, and Taiwan. [6][7][8][9][10][11][12][13][14][15][16][17] Spontaneous, voluntary reporting systems such as the United States Food and Drug Administration Adverse Event Reporting System (FAERS) database serve as a valuable resource for identifying rare side effects that are less likely to emerge during costly, time-limited clinical trials enrolling homogeneous patient populations of limited size. A limitation of FAERS and similar databases is the lack of reliable exposure information as well as a control group, but this can be partially overcome through the use of disproportionality analysis.…”
Section: Introductionmentioning
confidence: 99%